THE FUNDAMENTAL PRINCIPLES OF RECUSAL OF A JUDGE AT COMMON LAW: RECENT DEVELOPMENTS - Matthew Chuks Okpaluba; Tumo Charles Maloka (Obiter, 2022)
The common-law principle that no one should be a judge in his or her own cause is the basis upon which the rule against bias or apprehension of bias was founded. In constitutional parlance, this translates into the requirement that a judge or anyone under a duty to decide anything must be impartial, which is, in turn, the foundation for the recusal of a judge in adjudication. This cardinal principle of adjudication has produced an abundant case law indicating the circumstances in which a judge should, or ought to, recuse him- or herself on the ground of bias or reasonable apprehension of bias in common-law jurisdictions. This article focuses on the fundamental principles guiding the notion of recusal in the common-law courts. There is, first, a presumption of judicial impartiality, which is the preliminary but important hurdle an applicant for recusal of a judge must overcome. The inquiry proceeds no further if this presumption is not successfully rebutted early in the proceeding. The second hurdle is the test for recusal that the facts put forward in support of the allegation of bias or apparent bias must meet. This test is a two-dimensional reasonable standard test of a reasonably informed observer who would reasonably entertain an apprehension that the judge would (not might) be biased towards one party in the case. This test enables a court to determine whether the allegation of lack of judicial impartiality in any given case could lead to the recusal of the judge. The discussion that ensues is based on decided cases selected from specific Commonwealth jurisdictions where such matters have recently been dealt with. Indeed, these cases show that recusal of a judge in adjudication is, in practical terms, the application of the common-law principle of natural justice that a person cannot be a judge in his or her own cause. It is also a clear manifestation of the age-old adage that justice must not only be done, but must manifestly and undoubtedly be seen to be done.